Preparation of petroleum-based graphene heat-conducting film, prepared product and application of petroleum-based graphene heat-conducting film

The graphene thermal conductivity film is prepared by petroleum-based materials, and the potassium permanganate oxidation and vacuum carbonization process are used to form a tightly packed structure, which solves the problem of low thermal conductivity caused by uneven graphite oxidation, and achieves efficient heat dissipation and high thermal conductivity.

CN119218982APending Publication Date: 2024-12-31PETROCHINA CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202310794939.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2024-12-31
Patent Text Reader

Abstract

The invention discloses a method for preparing a graphene heat-conducting film, which comprises the following steps: 1) adding petroleum coke powder into concentrated sulfuric acid, adding potassium permanganate, and reacting to obtain oxidized petroleum coke; and 2) dispersing the oxidized petroleum coke prepared in the step 1) in deionized water, and homogenizing into single-layer oxidized petroleum coke slurry. According to the invention, the technical defect of low heat conductivity coefficient of the graphene film caused by non-uniform graphite oxidation in the prior art is at least partially overcome.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the preparation of a petroleum-based graphene thermal conductive film and the products prepared therefrom and applications thereof. Background Art

[0002] In the process of device heat dissipation, heat needs to be transferred from the inside of the device through the device packaging material and the heat sink interface and then through the heat sink to the external environment. Because the solid surface is rough and uneven on a microscopic scale, even if the contact pressure between the two solid surfaces is as high as 10MPa, the actual contact area only accounts for 1-2% of the apparent contact area, and the rest is tiny pores filled with air. In order to reduce the interfacial thermal resistance, people have developed thermally conductive interface materials. Filling the interface thermal conductive material between the contact surfaces can remove the air in the pores of the contact interface, forming a continuous heat conduction channel on the entire contact interface, and improving the heat dissipation efficiency.

[0003] The inventors prepared a graphene thermally conductive film with reference to the prior arts such as CN 114774087 A, CN 210578669 U, CN 215321191 U and CN 108819360A, and found that the thermal conductivity of the graphene film was low due to uneven oxidation of graphite. Summary of the invention

[0004] The present invention aims to at least partially overcome the technical defect of low thermal conductivity of graphene film caused by uneven graphite oxidation in the prior art.

[0005] The graphene thermal conductive film prepared in the embodiment of the present invention has excellent physical properties such as thermodynamics, and has strong application value in electronic products, especially as a heat dissipation material for processor chips in electronic products such as mobile phones and tablets.

[0006] As one aspect of the present invention, it relates to a method for preparing a petroleum-based graphene thermal conductive film, comprising:

[0007] 1) Take petroleum coke powder and add it into concentrated sulfuric acid, then add potassium permanganate to react and obtain oxidized petroleum coke.

[0008] 2) dispersing the oxidized petroleum coke prepared in step 1) in deionized water and homogenizing to form an oxidized petroleum coke slurry.

[0009] In a specific embodiment, the above method further includes:

[0010] 3) Preparation of oxidized petroleum coke membrane

[0011] The oxidized petroleum coke slurry is degassed by using a vacuum degassing system, and then coated and dried to obtain an oxidized petroleum coke film.

[0012] In a specific embodiment, the above method further includes:

[0013] 4) Carbonization and graphitization of oxidized petroleum coke films

[0014] Under nitrogen atmosphere, the oxidized petroleum coke film obtained in step 3) is sandwiched between two layers of graphite paper, baked and carbonized at 600-1100°C, and graphitized at 2800-3100°C. The petroleum coke is subjected to high-temperature graphitization, and graphitization reduces the oxidized graphite coke and rearranges the carbon atoms to form graphene that is tightly stacked into a two-dimensional hexagonal honeycomb lattice structure, and stacks to form a graphene film; in addition, the reduction process of the oxidized petroleum coke produces gas, resulting in a relatively fluffy graphene film. The high-temperature graphitization process can also remove impurities, increase purity, improve thermal conductivity and reduce the thermal expansion coefficient.

[0015] In a specific embodiment, the above method further includes:

[0016] 5) Graphene film calendering

[0017] Under vacuum conditions, a flat pressing process is used to maintain a pressure of 100 MPa for 10 minutes to compact the expanded graphene film and remove the gas generated between the graphene layers due to expansion, thereby obtaining a flexible and highly thermally conductive graphene heat dissipation film.

[0018] In a specific embodiment, the step 1) is:

[0019] The petroleum coke is oxidized by a modified Hummer method, specifically, the petroleum coke is mixed evenly with the concentrated sulfuric acid at a volume ratio of 10 to 60 ml / g of concentrated sulfuric acid to the mass ratio of petroleum coke, potassium permanganate is added in a water bath, wherein the mass ratio of potassium permanganate to petroleum coke is 1 to 3, the temperature is raised to 20 to 100° C. and the reaction is carried out for 0.2 to 6 hours, distilled water is added at a volume ratio of 10 to 100 ml / g of distilled water to the mass ratio of petroleum coke, the reaction is carried out at 70 to 100° C. for 10 to 70 minutes, and the oxidation reaction is terminated by dilution with distilled water, wherein the volume ratio of distilled water added to the mass ratio of petroleum coke is 50 to 200 ml / g, and finally a certain amount of hydrogen peroxide is added to remove excess potassium permanganate, and the oxidized petroleum coke system is washed to a pH between 4 and 6.

[0020] In a specific embodiment, the step 2) is:

[0021] The oxidized petroleum coke prepared in step 1) is dispersed in deionized water to prepare an oxidized petroleum coke suspension with a mass concentration of 50 to 100 g / L. The oxidized petroleum coke suspension is peeled off by a high-pressure homogenizer. The oxidized petroleum coke is homogenized under a pressure of 30 to 120 MPa to achieve single-layer peeling. The size of the oxidized petroleum coke is 0.1 to 0.9 μm. A uniform and stable oxidized petroleum coke slurry is obtained, and the slurry viscosity is controlled at 50,000 to 350,000 mPa·S.

[0022] As another aspect of the present invention, it relates to a petroleum-based graphene thermal conductive film prepared by the above method, wherein the Raman spectroscopy analysis of the petroleum-based graphene thermal conductive film is as follows: D / I G =0.01~0.03, density is 1.8~2.1g / cm 3 As a preference, the petroleum-based graphene thermal conductive film has a Raman spectrum ID / IG=0.01 and a density of 2.1 g / cm 3 .

[0023] As another aspect of the present invention, it involves the application of the above-mentioned petroleum-based graphene thermal conductive film in electronic products (such as 5G mobile phones, ultra-thin laptops, tablets, fanless design laptops, 5G communication base stations, wireless charging, LED lighting equipment, medical equipment, new energy vehicle power batteries, etc.).

[0024] As another aspect of the present invention, it relates to an electronic product, which uses the above-mentioned petroleum-based graphene thermal conductive film.

[0025] The present invention obtains a slurry with a higher solid content (~10%), while the existing commercial products are only about 5%. Petroleum coke is a carbon material with a needle-shaped or granular structure containing tiny graphite crystals. Oxidized petroleum coke with a size of less than 0.5 μm can be obtained by oxidation. The small-sized oxidized petroleum coke can effectively reduce the viscosity of the oxidized petroleum coke slurry. In the original commercial products, multiple layers need to be stacked to achieve a certain thickness. In the later stage of multi-layer stacking, the graphene film is prone to stratification.

[0026] The invention improves production efficiency and reduces costs, and effectively improves thermal conductivity. The high-concentration slurry of the invention can effectively increase the thickness of the oxidized petroleum coke film, eliminating the multi-layer lamination process, and the density of the obtained graphene thermal conductive film can reach 1.8-2.1 g / cm 3 , the thickness is adjustable in the range of 10 to 500 μm; in addition, using petroleum coke as raw material, oxidized petroleum coke with uniform oxidation degree and small defects was obtained, so the thermal conductivity of graphene reached 1700 W / (m·K). DETAILED DESCRIPTION

[0027] The inventors found that the current graphite oxides are all obtained by oxidation of natural flake graphite as raw material. The layer-to-layer structure of natural flake graphite is relatively dense. The oxidation mechanism starts from the boundary. As the oxidation proceeds, the interlayer spacing increases, and the oxidant is able to penetrate between the layers of graphite. Therefore, the oxidation process extends from the boundary of the graphite to the middle. In such a reaction process, the boundary oxidation starts first, and the oxidant concentration is the highest. As the oxidant is consumed, the degree of oxidation gradually decreases from the boundary to the middle position. Such an oxidation process is difficult to achieve uniform oxidation of graphite.

[0028] The thermal conductivity of graphene films is currently difficult to improve, mainly because it is difficult to obtain high-quality graphene oxide films, which requires graphene oxide to have high oxidizability and dispersibility. However, high oxidizability is also accompanied by a large number of surface defects, and the subsequent graphitization process is difficult to completely repair so many defects.

[0029] The present invention uses petroleum coke instead of natural flake graphite as raw material. Before the temperature reaction, the oxidant is uniformly infiltrated into the petroleum coke, and the petroleum coke is uniformly oxidized, which effectively overcomes the problem that the current flake graphite cannot be uniformly oxidized. The current graphene membrane has problems such as low yield rate of different batches of products, unstable membrane structure, easy cracks and large differences in thermal conductivity. The main reason is that the oxidation degree of the raw materials is not uniform. Uniformly oxidized graphite can effectively improve the efficiency of homogenization and the stability of the oxidized graphene slurry, and ultimately improve the batch stability and thermal conductivity of the graphene membrane.

[0030] The inventors prepared graphene quantum dots with reference to the prior art documents including CN 108996492 A. Liquid petroleum was used as the raw material, and graphene quantum dots were obtained by oxidation, separation and purification. The size distribution was 1 to 5 nm. The size was too small, and the product was distributed in the supernatant. The yield was low, so the concentration was low and the graphene membrane structure could not be prepared by coating technology. In addition, the high-speed centrifugation process and dialysis process involved in the preparation process of graphene quantum dots are also difficult to scale up by engineering.

[0031] The present invention uses solid petroleum coke as raw material. The petroleum coke of the present invention is completely converted into oxidized petroleum coke with high yield. The oxidation, separation and stripping process technologies adopted are simple and easy to operate and suitable for engineering scale-up.

[0032] Source of raw materials or equipment:

[0033] Petroleum coke: PetroChina Company Limited.

[0034] Crusher (Shenzhen Leitong Industrial Co., Ltd. small crusher, model DFT1000), sand mill (Changzhou Longxin Chemical Machinery Co., Ltd., WSP-60L / 6L): Changzhou University.

[0035] Sulfuric acid, potassium permanganate, hydrogen peroxide: AR pure, Sinopharm Group.

[0036] Evaluation and analysis methods: rotational viscosity measurement (digital rotational viscometer NDJ-8S, GB / T 9269-1988), thermal conductivity measurement (German NETZSCH laser thermal conductivity meter, ASTM E1461), density measurement (drainage density test method).

[0037] Embodiment 1:

[0038] 1) Preparation of oxidized petroleum coke

[0039] The petroleum coke is processed by a crusher and a sand mill to obtain a petroleum coke powder with a size of less than 10 μm. 1 kg of petroleum coke is mixed with 30 L of 98% sulfuric acid by mass concentration, and then 3 kg of potassium permanganate is quickly added in a 15°C water bath and mixed evenly. The system temperature is kept at 0-20°C during the addition of potassium permanganate. Then the system temperature is raised to 40°C and reacted for 3 hours. Then 30 L of deionized water is added, and the system temperature is raised to 80°C for reaction for 30 minutes. Then, 200 L of deionized water and 3 L of hydrogen peroxide (30 wt%) are used to reduce the excess potassium permanganate, and the precipitate is centrifuged and washed to a pH of 5 to obtain oxidized petroleum coke.

[0040] 2) Preparation of oxidized petroleum coke slurry

[0041] The oxidized petroleum coke prepared in step 1 is dispersed in deionized water to prepare 50 L of oxidized petroleum coke suspension with a mass concentration of 100 g / L. The oxidized petroleum coke dispersion is homogenized once under a pressure of 120 MPa to achieve monolayer peeling to obtain a uniform and stable oxidized petroleum coke slurry with a viscosity controlled at 200,000 mPa·s, good fluidity, and easy coating.

[0042] 3) Preparation of oxidized petroleum coke membrane

[0043] First, the oxidized petroleum coke slurry was degassed using a vacuum degassing system. Then, it was transported to a comma coater through a pipeline and coated on a polypropylene substrate. The coating thickness was 5 mm, the speed was 5 m / min, the drying temperature was 100°C, and the drying time was 20 min. The dried oxidized petroleum coke film was peeled off from the polypropylene substrate and sliced ​​to obtain a 500 μm oxidized petroleum coke film.

[0044] 4) Carbonization and graphitization of oxidized petroleum coke films

[0045] First, under a nitrogen atmosphere, the oxidized petroleum coke film was sandwiched between two layers of graphite paper, placed in an oven, and heated to 600°C at a rate of 0.5°C / min and kept warm for 5 hours. Then, under a nitrogen atmosphere, in a graphitization furnace, the temperature was raised to 3100°C at a rate of 30°C / min, kept warm for 0.5 hours, and naturally cooled to obtain an expanded graphene film.

[0046] 5) Graphene film calendering

[0047] Under vacuum conditions, the flat pressing process was used to maintain a pressure of 100 MPa for 10 minutes to compact the expanded graphene film and remove the gas generated between the graphene layers due to expansion, thus obtaining a flexible and highly thermally conductive graphene heat dissipation film. Raman spectrum I D / I G =0.01, density is 1.8g / cm 3, thickness is 200μm, and thermal conductivity is 1667W / (m·K).

[0048] Embodiment 2:

[0049] 1) Preparation of oxidized petroleum coke

[0050] The petroleum coke was processed by a crusher and a sand mill to obtain a petroleum coke powder with a size of less than 10 μm. 1 kg of petroleum coke was mixed with 30 L of 98% sulfuric acid by mass, and then 3 kg of potassium permanganate was quickly added in a 15°C water bath and mixed evenly. The system temperature was kept at 0-20°C during the addition of potassium permanganate. Then the system temperature was raised to 40°C and reacted for 3 hours. Then 30 L of deionized water was added, and the system temperature was raised to 80°C for reaction for 30 minutes. Then 200 L of deionized water and 3 L of hydrogen peroxide (30 wt%) were used to reduce the excess potassium permanganate, and the solution was centrifuged and washed until the pH was 5.

[0051] 2) Preparation of oxidized petroleum coke slurry

[0052] The oxidized petroleum coke prepared in step 1 is dispersed in deionized water to prepare 50 L of oxidized petroleum coke suspension with a mass concentration of 100 g / L. The oxidized petroleum coke dispersion is homogenized once under a pressure of 120 MPa to achieve monolayer peeling to obtain a uniform and stable oxidized petroleum coke slurry with a viscosity controlled at 200,000 mPa·s, good fluidity, and easy coating.

[0053] 3) Preparation of oxidized petroleum coke membrane

[0054] First, the oxidized petroleum coke slurry was degassed using a vacuum degassing system. Then, it was transported to a comma coater through a pipeline and coated on a polypropylene substrate. The coating thickness was 5 mm, the speed was 5 m / min, the drying temperature was 100°C, and the drying time was 20 min. The dried oxidized petroleum coke film was peeled off from the polypropylene substrate and sliced ​​to obtain a 500 μm oxidized petroleum coke film.

[0055] 4) Carbonization and graphitization of oxidized petroleum coke films

[0056] First, under a nitrogen atmosphere, the oxidized petroleum coke film was sandwiched between two layers of graphite paper, placed in an oven, and heated to 600°C at a rate of 0.5°C / min and kept warm for 5 hours. Then, under a nitrogen atmosphere, in a graphitization furnace, the temperature was raised to 3100°C at a rate of 30°C / min, kept warm for 0.5 hours, and naturally cooled to obtain an expanded graphene film.

[0057] 5) Graphene film calendering

[0058] Under vacuum conditions, the flat pressing process was used to maintain a pressure of 50 MPa for 60 minutes to compact the expanded graphene film and remove the gas generated between the graphene layers due to expansion, thus obtaining a flexible and highly thermally conductive graphene heat dissipation film with a Raman spectrum of ID / IG=0.03 and a density of 1.9 g / cm 3 , thickness is 130μm, and thermal conductivity is 1612W / (m·K).

[0059] Embodiment 3:

[0060] 1) Preparation of oxidized petroleum coke

[0061] The petroleum coke was processed by a crusher and a sand mill to obtain a petroleum coke powder with a size of less than 10 μm. 1 kg of petroleum coke was mixed with 30 L of 98% sulfuric acid by mass, and then 3 kg of potassium permanganate was quickly added in a 15°C water bath and mixed evenly. The system temperature was kept at 0-20°C during the addition of potassium permanganate. Then the system temperature was raised to 40°C and reacted for 3 hours. Then 30 L of deionized water was added, and the system temperature was raised to 80°C for reaction for 30 minutes. Then 200 L of deionized water and 3 L of hydrogen peroxide (30 wt%) were used to reduce the excess potassium permanganate, and the solution was centrifuged and washed until the pH was 5.

[0062] 2) Preparation of oxidized petroleum coke slurry

[0063] The oxidized petroleum coke prepared in step 1 is dispersed in deionized water to prepare 50 L of oxidized petroleum coke suspension with a mass concentration of 100 g / L. The oxidized petroleum coke dispersion is homogenized once under a pressure of 120 MPa to achieve monolayer peeling to obtain a uniform and stable oxidized petroleum coke slurry with a viscosity controlled at 200,000 mPa·s, good fluidity, and easy coating.

[0064] 3) Preparation of oxidized petroleum coke membrane

[0065] First, the oxidized petroleum coke slurry was degassed using a vacuum degassing system. Then, it was transported to a comma coater through a pipeline and coated on a polypropylene substrate. The coating thickness was 5 mm, the speed was 5 m / min, the drying temperature was 100°C, and the drying time was 20 min. The dried oxidized petroleum coke film was peeled off from the polypropylene substrate and sliced ​​to obtain a 500 μm oxidized petroleum coke film.

[0066] 4) Carbonization and graphitization of oxidized petroleum coke films

[0067] First, under a nitrogen atmosphere, the oxidized petroleum coke film was sandwiched between two layers of graphite paper, placed in an oven, and heated to 600°C at a rate of 0.5°C / min and kept warm for 5 hours. Then, under a nitrogen atmosphere, in a graphitization furnace, the temperature was raised to 3100°C at a rate of 30°C / min, kept warm for 0.5 hours, and naturally cooled to obtain an expanded graphene film.

[0068] 5) Graphene film calendering

[0069] Under vacuum conditions, the flat pressing process was used to maintain a pressure of 80 MPa for 30 minutes to compact the expanded graphene film and remove the gas generated between the graphene layers due to expansion, thus obtaining a flexible and highly thermally conductive graphene heat dissipation film with a Raman spectrum of ID / IG=0.02 and a density of 2.1 g / cm 3 , thickness is 90μm, and thermal conductivity is 1596W / (m·K).

[0070] Embodiment 4:

[0071] 1) Preparation of oxidized petroleum coke

[0072] The petroleum coke was processed by a crusher and a sand mill to obtain a petroleum coke powder with a size of less than 10 μm. 1 kg of petroleum coke was mixed with 30 L of 98% sulfuric acid by mass, and then 3 kg of potassium permanganate was quickly added in a 15°C water bath and mixed evenly. The system temperature was kept at 0-20°C during the addition of potassium permanganate. Then the system temperature was raised to 40°C and reacted for 3 hours. Then 30 L of deionized water was added, and the system temperature was raised to 80°C for reaction for 30 minutes. Then 200 L of deionized water and 3 L of hydrogen peroxide (30 wt%) were used to reduce the excess potassium permanganate, and the solution was centrifuged and washed until the pH was 5.

[0073] 2) Preparation of oxidized petroleum coke slurry

[0074] The oxidized petroleum coke prepared in step 1 is dispersed in deionized water to prepare 50 L of oxidized petroleum coke suspension with a mass concentration of 100 g / L. The oxidized petroleum coke dispersion is homogenized once under a pressure of 120 MPa to achieve monolayer peeling to obtain a uniform and stable oxidized petroleum coke slurry with a viscosity controlled at 200,000 mPa·s, good fluidity, and easy coating.

[0075] 3) Preparation of oxidized petroleum coke membrane

[0076] First, the oxidized petroleum coke slurry was degassed using a vacuum degassing system. Then, it was transported to a comma coater through a pipeline and coated on a polypropylene substrate. The coating thickness was 5 mm, the speed was 5 m / min, the drying temperature was 100°C, and the drying time was 20 min. The dried oxidized petroleum coke film was peeled off from the polypropylene substrate and sliced ​​to obtain a 500 μm oxidized petroleum coke film.

[0077] 4) Carbonization and graphitization of oxidized petroleum coke films

[0078] First, under a nitrogen atmosphere, the oxidized petroleum coke film was sandwiched between two layers of graphite paper, placed in an oven, and heated to 600°C at a rate of 0.5°C / min and kept warm for 5 hours. Then, under a nitrogen atmosphere, in a graphitization furnace, the temperature was raised to 3100°C at a rate of 30°C / min, kept warm for 0.5 hours, and naturally cooled to obtain an expanded graphene film.

[0079] 5) Graphene film calendering

[0080] Under vacuum conditions, the flat pressing process was used to maintain a pressure of 100 MPa for 60 minutes to compact the expanded graphene film and remove the gas generated between the graphene layers due to expansion, thus obtaining a flexible and highly thermally conductive graphene heat dissipation film with a Raman spectrum of ID / IG=0.01 and a density of 2.1 g / cm 3 , thickness is 500μm, and thermal conductivity is 1712W / (m·K).

[0081] Embodiment 5:

[0082] 1) Preparation of oxidized petroleum coke

[0083] The petroleum coke was processed by a crusher and a sand mill to obtain a petroleum coke powder with a size of less than 10 μm. 1 kg of petroleum coke was mixed with 30 L of 98% sulfuric acid by mass, and then 3 kg of potassium permanganate was quickly added in a 15°C water bath and mixed evenly. The system temperature was kept at 0-20°C during the addition of potassium permanganate. Then the system temperature was raised to 40°C and reacted for 3 hours. Then 30 L of deionized water was added, and the system temperature was raised to 80°C for reaction for 30 minutes. Then 200 L of deionized water and 3 L of hydrogen peroxide (30 wt%) were used to reduce the excess potassium permanganate, and the solution was centrifuged and washed until the pH was 5.

[0084] 2) Preparation of oxidized petroleum coke slurry

[0085] The oxidized petroleum coke prepared in step 1 is dispersed in deionized water to prepare 50 L of oxidized petroleum coke suspension with a mass concentration of 100 g / L. The oxidized petroleum coke dispersion is homogenized once under a pressure of 120 MPa to achieve monolayer peeling to obtain a uniform and stable oxidized petroleum coke slurry with a viscosity controlled at 200,000 mPa·s, good fluidity, and easy coating.

[0086] 3) Preparation of oxidized petroleum coke membrane

[0087] First, the oxidized petroleum coke slurry was degassed using a vacuum degassing system. Then, it was transported to a comma coater through a pipeline and coated on a polypropylene substrate. The coating thickness was 5 mm, the speed was 5 m / min, the drying temperature was 100°C, and the drying time was 20 min. The dried oxidized petroleum coke film was peeled off from the polypropylene substrate and sliced ​​to obtain a 500 μm oxidized petroleum coke film.

[0088] 4) Carbonization and graphitization of oxidized petroleum coke films

[0089] First, under a nitrogen atmosphere, the oxidized petroleum coke film was sandwiched between two layers of graphite paper, placed in an oven, and heated to 600°C at a rate of 0.5°C / min and kept warm for 5 hours. Then, under a nitrogen atmosphere, in a graphitization furnace, the temperature was raised to 3100°C at a rate of 30°C / min, kept warm for 0.5 hours, and naturally cooled to obtain an expanded graphene film.

[0090] 5) Graphene film calendering

[0091] Under vacuum conditions, the flat pressing process was used to maintain a pressure of 60 MPa for 60 minutes to compact the expanded graphene film and remove the gas generated between the graphene layers due to expansion, thus obtaining a flexible and highly thermally conductive graphene heat dissipation film. Raman spectroscopy analysis showed that ID / IG=0.02 and the density was 2.0 g / cm 3 , thickness is 290μm, and thermal conductivity is 1616W / (m·K).

[0092] Embodiment 6:

[0093] 1) Preparation of oxidized petroleum coke

[0094] The petroleum coke was processed by a crusher and a sand mill to obtain a petroleum coke powder with a size of less than 10 μm. 1 kg of petroleum coke was mixed with 10 L of 90% sulfuric acid by mass concentration, and then 1 kg of potassium permanganate was quickly added in a 5°C water bath and mixed evenly. The system temperature was kept at 0-20°C during the addition of potassium permanganate. Then the system temperature was raised to 70°C and reacted for 30 minutes. Then 80 L of deionized water was added, and the system temperature was raised to 95°C for reaction for 10 minutes. Then 50 L of deionized water and 3 L of hydrogen peroxide (30 wt%) were used to reduce the excess potassium permanganate, and the solution was washed by centrifugation until the pH was 6.

[0095] 2) Preparation of oxidized petroleum coke slurry

[0096] The graphite oxide prepared in step 1 was dispersed in deionized water to prepare 100 L of graphite oxide suspension with a mass concentration of 50 g / L. The oxidized petroleum coke dispersion was homogenized twice under a pressure of 80 MPa to achieve monolayer peeling to obtain a uniform and stable oxidized petroleum coke slurry with a viscosity controlled at 100,000 mPa·s, good fluidity, and easy coating.

[0097] 3) Preparation of oxidized petroleum coke membrane

[0098] Firstly, a vacuum degassing system was used to degas the oxidized petroleum coke slurry. Then, it was transported to a comma coater through a pipeline and coated on a polypropylene substrate. The coating thickness was 10 mm, the speed was 1 m / min, the drying temperature was 80°C, and the drying time was 60 min. The dried oxidized petroleum coke film was peeled off from the polypropylene substrate and sliced ​​to obtain a 310 μm oxidized petroleum coke film.

[0099] 4) Carbonization and graphitization of oxidized petroleum coke films

[0100] First, under a nitrogen atmosphere, the oxidized petroleum coke film was sandwiched between two layers of graphite paper, placed in an oven, and heated to 1000°C at a rate of 5°C / min and kept warm for 1 hour; then, under an argon atmosphere, in a graphitization furnace, the temperature was raised to 2800°C at a rate of 20°C / min, kept warm for 2 hours, and naturally cooled to obtain an expanded graphene film.

[0101] 5) Graphene film calendering

[0102] Under vacuum conditions, the flat pressing process was used to maintain a pressure of 100 MPa for 60 minutes to compact the expanded graphene film and remove the gas generated between the graphene layers due to expansion, thus obtaining a flexible and highly thermally conductive graphene heat dissipation film with a Raman spectrum of ID / IG=0.02 and a density of 1.9 g / cm 3 , thickness is 130μm, and thermal conductivity is 1606W / (m·K).

[0103] Embodiment 7:

[0104] 1) Preparation of oxidized petroleum coke

[0105] The petroleum coke was processed by a crusher and a sand mill to obtain a petroleum coke powder with a size of less than 10 μm. 500 g of petroleum coke was mixed with 10 L of 95% sulfuric acid by mass, and then 1 kg of potassium permanganate was quickly added in a 0°C water bath and mixed evenly. The system temperature was kept at 0-20°C during the addition of potassium permanganate. Then the system temperature was raised to 50°C, and the reaction was continued for 1 hour. Then 15 L of deionized water was added, and the system temperature was raised to 75°C for reaction for 30 minutes. Then, 25 L of deionized water and 1 L of hydrogen peroxide (30 wt%) were used to reduce the excess potassium permanganate, and the solution was washed by centrifugation until the pH was 5.

[0106] 2) Preparation of oxidized petroleum coke slurry

[0107] The graphite oxide prepared in step 1 was dispersed in deionized water to prepare 100 L of graphite oxide suspension with a mass concentration of 80 g / L. The oxidized petroleum coke dispersion was homogenized three times under a pressure of 60 MPa to achieve monolayer peeling to obtain a uniform and stable oxidized petroleum coke slurry with a viscosity controlled at 200,000 mPa·s, good fluidity, and easy coating.

[0108] 3) Preparation of oxidized petroleum coke membrane

[0109] Firstly, a vacuum degassing system was used to degas the oxidized petroleum coke slurry. Then, the oxidized petroleum coke slurry was transported to a comma coater through a pipeline and coated on a polyester substrate. The coating thickness was 5 mm, the speed was 1 m / min, the drying temperature was 50°C, and the drying time was 60 min. The dried oxidized petroleum coke film was peeled off from the polypropylene substrate and sliced ​​to obtain a 250 μm oxidized petroleum coke film.

[0110] 4) Carbonization and graphitization of oxidized petroleum coke films

[0111] Firstly, in an argon-hydrogen mixed atmosphere, the oxidized petroleum coke film was sandwiched between two layers of graphite paper, placed in an oven, and heated to 800°C at a rate of 5°C / min and kept warm for 1 hour; then, in an argon atmosphere, in a graphitization furnace, the temperature was raised to 3000°C at a rate of 30°C / min, kept warm for 1 hour, and naturally cooled to obtain an expanded graphene film.

[0112] 5) Graphene film calendering

[0113] Under vacuum conditions, the flat pressing process was used to maintain a pressure of 100 MPa for 60 minutes to compact the expanded graphene film and remove the gas generated between the graphene layers due to expansion, thus obtaining a flexible and highly thermally conductive graphene heat dissipation film with a Raman spectrum of ID / IG=0.02 and a density of 2.0 g / cm 3 , thickness is 100μm, and thermal conductivity is 1674W / (m·K).

[0114] Embodiment 8:

[0115] 1) Preparation of petroleum-based graphite oxide

[0116] The petroleum coke was processed by a crusher and a sand mill to obtain a petroleum coke powder with a size of less than 10 μm. 500 g of petroleum coke was mixed with 10 L of 98% sulfuric acid by mass, and then 1 kg of potassium permanganate was quickly added in a 0°C water bath and mixed evenly. The system temperature was kept at 0-20°C during the addition of potassium permanganate. Then the system temperature was raised to 60°C and reacted for 1 hour. Then 40 L of deionized water was added, and the system temperature was raised to 90°C for reaction for 20 minutes. Then, 100 L of deionized water and 1.5 L of hydrogen peroxide (30 wt%) were used to reduce the excess potassium permanganate, and the solution was washed by centrifugation until the pH was 5.

[0117] 2) Preparation of oxidized petroleum coke slurry

[0118] The graphite oxide prepared in step 1 was dispersed in deionized water to prepare 50 L of graphite oxide suspension with a mass concentration of 100 g / L. The oxidized petroleum coke dispersion was homogenized 5 times under a pressure of 30 MPa to achieve monolayer peeling to obtain a uniform and stable oxidized petroleum coke slurry with a viscosity controlled at 300,000 mPa·s, good fluidity, and easy coating.

[0119] 3) Preparation of oxidized petroleum coke membrane

[0120] First, a vacuum degassing system was used to degas the oxidized petroleum coke slurry. Then, the oxidized petroleum coke slurry was transported to a comma coater through a pipeline and coated on a polyester substrate. The coating thickness was 10 mm, the speed was 1 m / min, the drying temperature was 100°C, and the drying time was 60 min. The dried oxidized petroleum coke film was peeled off from the polypropylene substrate and sliced ​​to obtain a 1 mm oxidized petroleum coke film.

[0121] 4) Carbonization and graphitization of oxidized petroleum coke films

[0122] Firstly, in an argon-hydrogen mixed atmosphere, the oxidized petroleum coke film was sandwiched between two layers of graphite paper, placed in an oven, and heated to 1000°C at a rate of 5°C / min and kept warm for 2 hours; then, in an argon atmosphere, in a graphitization furnace, the temperature was raised to 3100°C at a rate of 30°C / min, kept warm for 2 hours, and naturally cooled to obtain an expanded graphene film.

[0123] 5) Graphene film calendering

[0124] Under vacuum conditions, the flat pressing process was used to maintain a pressure of 100 MPa for 60 minutes to compact the expanded graphene film and remove the gas generated between the graphene layers due to expansion, thus obtaining a flexible and highly thermally conductive graphene heat dissipation film with a Raman spectrum of ID / IG=0.01 and a density of 2.0 g / cm 3 , thickness is 500μm, and thermal conductivity is 1639W / (m·K).

[0125] Embodiment 9:

[0126] 1) Preparation of oxidized petroleum coke

[0127] The petroleum coke was processed by a crusher and a sand mill to obtain a petroleum coke powder with a size of less than 10 μm. 1 kg of petroleum coke was mixed with 20 L of 95% sulfuric acid by mass, and then 2 kg of potassium permanganate was quickly added in a 20°C water bath and mixed evenly. The system temperature was kept at 0-20°C during the addition of potassium permanganate. Then the system temperature was raised to 50°C and reacted for 2 hours. Then 50 L of deionized water was added, and the system temperature was raised to 90°C for reaction for 30 minutes. Then 100 L of deionized water and 3 L of hydrogen peroxide (30 wt%) were used to reduce the excess potassium permanganate, and the solution was washed by centrifugation until the pH was 6.

[0128] 2) Preparation of oxidized petroleum coke slurry

[0129] The graphite oxide filter cake was dispersed in deionized water to prepare 100 L of graphite oxide suspension with a mass concentration of 100 g / L. The oxidized petroleum coke dispersion was homogenized 4 times under a pressure of 50 MPa to achieve single-layer peeling and obtain a uniform and stable oxidized petroleum coke slurry with a viscosity controlled at 250,000 mPa·s, good fluidity, and easy coating.

[0130] 3) Preparation of oxidized petroleum coke membrane

[0131] Firstly, a vacuum degassing system was used to degas the oxidized petroleum coke slurry. Then, the oxidized petroleum coke slurry was transported to a comma coater through a pipeline and coated on a polyester substrate. The coating thickness was 10 mm, the speed was 5 m / min, the drying temperature was 80°C, and the drying time was 40 min. The dried oxidized petroleum coke film was peeled off from the polypropylene substrate and sliced ​​to obtain a 700 μm oxidized petroleum coke film.

[0132] 4) Carbonization and graphitization of oxidized petroleum coke films

[0133] First, under a helium atmosphere, the oxidized petroleum coke film was sandwiched between two layers of graphite paper, placed in an oven, and heated to 1100°C at a rate of 10°C / min and kept warm for 2 hours. Then, under an argon atmosphere, in a graphitization furnace, the temperature was raised to 3000°C at a rate of 20°C / min, kept warm for 1 hour, and naturally cooled to obtain an expanded graphene film.

[0134] 5) Graphene film calendering

[0135] Under vacuum conditions, the flat pressing process was used to maintain a pressure of 100 MPa for 60 minutes to compact the expanded graphene film and remove the gas generated between the graphene layers due to expansion, thus obtaining a flexible and highly thermally conductive graphene heat dissipation film with a Raman spectrum of ID / IG=0.02 and a density of 2.0 g / cm 3 , thickness is 290μm, and thermal conductivity is 1671W / (m·K).

[0136] Embodiment 10:

[0137] 1) Preparation of oxidized petroleum coke

[0138] The petroleum coke was processed by a crusher and a sand mill to obtain a petroleum coke powder with a size of less than 10 μm. 1 kg of petroleum coke was mixed with 20 L of 95% sulfuric acid by mass, and then 2 kg of potassium permanganate was quickly added in a 20°C water bath and mixed evenly. The system temperature was kept at 0-20°C during the addition of potassium permanganate. Then the system temperature was raised to 50°C and reacted for 2 hours. Then 50 L of deionized water was added, and the system temperature was raised to 90°C for reaction for 30 minutes. Then 100 L of deionized water and 3 L of hydrogen peroxide (30 wt%) were used to reduce the excess potassium permanganate, and the solution was washed by centrifugation until the pH was 6.

[0139] 2) Preparation of oxidized petroleum coke slurry

[0140] The graphite oxide filter cake was dispersed in deionized water to prepare 100 L of graphite oxide suspension with a mass concentration of 100 g / L. The oxidized petroleum coke dispersion was homogenized 4 times under a pressure of 50 MPa to achieve single-layer peeling and obtain a uniform and stable oxidized petroleum coke slurry with a viscosity controlled at 250,000 mPa·s, good fluidity, and easy coating.

[0141] 3) Preparation of oxidized petroleum coke membrane

[0142] Firstly, a vacuum degassing system was used to degas the oxidized petroleum coke slurry. Then, the oxidized petroleum coke slurry was transported to a comma coater through a pipeline and coated on a polyester substrate. The coating thickness was 8 mm, the speed was 5 m / min, the drying temperature was 80°C, and the drying time was 40 min. The dried oxidized petroleum coke film was peeled off from the polypropylene substrate and sliced ​​to obtain a 600 μm oxidized petroleum coke film.

[0143] 4) Carbonization and graphitization of oxidized petroleum coke films

[0144] First, under a helium atmosphere, the oxidized petroleum coke film was sandwiched between two layers of graphite paper, placed in an oven, and heated to 1100°C at a rate of 10°C / min and kept warm for 2 hours. Then, under an argon atmosphere, in a graphitization furnace, the temperature was raised to 3000°C at a rate of 20°C / min, kept warm for 2 hours, and naturally cooled to obtain an expanded graphene film.

[0145] 5) Graphene film calendering

[0146] Under vacuum conditions, the flat pressing process was used to maintain a pressure of 100 MPa for 60 minutes to compact the expanded graphene film and remove the gas generated between the graphene layers due to expansion, thus obtaining a flexible and highly thermally conductive graphene heat dissipation film with a Raman spectrum of ID / IG=0.01 and a density of 2.0 g / cm 3 , thickness is 240μm, and thermal conductivity is 1629W / (m·K).

[0147] Comparative Example 1:

[0148] (1) Prepare a roll of polyimide (PI) film with an area of ​​5.2 m 2 , thickness is 20 μm;

[0149] (2) placing the polyimide (PI) film in a carbonization furnace and carbonizing it at 800°C for 3 h under vacuum;

[0150] (3) placing the polyimide (PI) film in a graphitization furnace, introducing argon as a protective gas, and applying a certain gas pressure (0.01-0.05 MPa), graphitizing at 2000° C. for 6 h to obtain a semi-finished thermal conductive film coil;

[0151] (4) The semi-finished thermal conductive film coil is calendered by a calender and sliced ​​by a slicer to obtain a thermal conductive film coil product of corresponding size and thickness, for example, a thickness of 23 μm;

[0152] (5) The finally prepared graphene thermal conductive film coil product is tested according to the standard, and the thermal conductivity coefficient obtained by the test is 1600 W / m·K.

[0153] Comparative Example 2:

[0154] 1) Preparation of graphite oxide

[0155] Take 1kg of natural graphite with a size of less than 10μm and mix it with 30L of sulfuric acid with a mass concentration of 98%, then quickly add 3kg of potassium permanganate in a 15℃ water bath and mix it evenly. Keep the system temperature at 0-20℃ during the process of adding potassium permanganate. Then raise the system temperature to 40℃ and react for 3h. Then add 30L of deionized water and raise the system temperature to 80℃ for 30min. Then use 200L of deionized water and 3L of hydrogen peroxide (30wt%) to reduce the excess potassium permanganate and wash it by centrifugation until the pH is 5.

[0156] 2) Preparation of graphene oxide slurry

[0157] The graphite oxide prepared in step 1 was dispersed in deionized water to prepare 50 L of a graphite oxide suspension with a mass concentration of 100 g / L. The graphite oxide dispersion was homogenized once under a pressure of 120 MPa to achieve monolayer exfoliation to obtain a uniform and stable graphene oxide slurry with a viscosity controlled at 500,000 mPa·s, good fluidity, and easy coating.

[0158] 3) Preparation of graphene oxide film

[0159] First, the graphene oxide slurry was degassed using a vacuum degassing system; then, it was transported to a comma coater through a pipeline and coated on a polypropylene substrate with a coating thickness of 5 mm, a speed of 5 m / min, a drying temperature of 100°C, and a drying time of 20 min; the dried graphene oxide film was peeled off from the polypropylene substrate and sliced ​​to obtain a 500 μm graphene oxide film.

[0160] 4) Carbonization and graphitization of graphene oxide films

[0161] First, under a nitrogen atmosphere, the oxidized ethylene film was sandwiched between two layers of graphite paper, placed in an oven, and heated to 600°C at a rate of 0.5°C / min and kept warm for 5 hours; then, under a nitrogen atmosphere, in a graphitization furnace, the temperature was raised to 3100°C at a rate of 30°C / min, kept warm for 0.5 hours, and naturally cooled to obtain an expanded graphene film.

[0162] 5) Graphene film calendering

[0163] Under vacuum conditions, the flat pressing process was used to maintain a pressure of 100 MPa for 60 minutes to compact the expanded graphene film and remove the gas generated between the graphene layers due to expansion, thus obtaining a flexible and highly thermally conductive graphene heat dissipation film with a Raman spectrum of ID / IG=0.01 and a density of 1.8 g / cm 3 , thickness is 500μm, and thermal conductivity is 1267W / (m·K).

[0164] Comparative Example 3:

[0165] 1) Preparation of graphite oxide

[0166] Take 1kg of artificial graphite with a size of less than 10μm and mix it with 30L of sulfuric acid with a mass concentration of 98%, then quickly add 3kg of potassium permanganate in a 15℃ water bath and mix it evenly. Keep the system temperature at 0-20℃ during the process of adding potassium permanganate. Then raise the system temperature to 40℃ and react for 3h. Then add 30L of deionized water and raise the system temperature to 80℃ for 30min. Then use 200L of deionized water and 3L of hydrogen peroxide (30wt%) to reduce the excess potassium permanganate and wash it by centrifugation until the pH is 5.

[0167] 2) Preparation of graphene oxide slurry

[0168] The graphite oxide prepared in step 1 was dispersed in deionized water to prepare 50 L of a graphite oxide suspension with a mass concentration of 100 g / L. The graphite oxide dispersion was homogenized once under a pressure of 120 MPa to achieve monolayer exfoliation to obtain a uniform and stable graphene oxide slurry with a viscosity controlled at 300,000 mPa·s, good fluidity, and easy coating.

[0169] 3) Preparation of graphene oxide film

[0170] First, the graphene oxide slurry was degassed using a vacuum degassing system; then, it was transported to a comma coater through a pipeline and coated on a polypropylene substrate with a coating thickness of 5 mm, a speed of 5 m / min, a drying temperature of 100°C, and a drying time of 20 min; the dried graphene oxide film was peeled off from the polypropylene substrate and sliced ​​to obtain a 500 μm graphene oxide film.

[0171] 4) Carbonization and graphitization of graphene oxide films

[0172] First, under a nitrogen atmosphere, the oxidized ethylene film was sandwiched between two layers of graphite paper, placed in an oven, and heated to 600°C at a rate of 0.5°C / min and kept warm for 5 hours; then, under a nitrogen atmosphere, in a graphitization furnace, the temperature was raised to 3100°C at a rate of 30°C / min, kept warm for 0.5 hours, and naturally cooled to obtain an expanded graphene film.

[0173] 5) Graphene film calendering

[0174] Under vacuum conditions, the flat pressing process was used to maintain a pressure of 100 MPa for 60 minutes to compact the expanded graphene film and remove the gas generated between the graphene layers due to expansion, thus obtaining a flexible and highly thermally conductive graphene heat dissipation film with a Raman spectrum of ID / IG=0.02 and a density of 1.8 g / cm 3 , thickness is 500μm, and thermal conductivity is 985W / (m·K).

[0175] Comparative Example 4:

[0176] 1) Preparation of graphite oxide

[0177] Take 1kg of expanded graphite with a size of less than 10μm and mix it with 30L of sulfuric acid with a mass concentration of 98%, then quickly add 3kg of potassium permanganate in a 15℃ water bath, mix evenly, and keep the system temperature at 0-20℃ during the process of adding potassium permanganate. Then raise the system temperature to 40℃, react for 3h, then add 30L of deionized water, and raise the system temperature to 80℃ for 30min, then use 200L of deionized water and 3L of hydrogen peroxide (30wt%) to reduce the excess potassium permanganate, and centrifuge and wash until the pH is 5.

[0178] 2) Preparation of graphene oxide slurry

[0179] The graphite oxide prepared in step 1 was dispersed in deionized water to prepare 50 L of a graphite oxide suspension with a mass concentration of 100 g / L. The graphite oxide dispersion was homogenized once under a pressure of 120 MPa to achieve monolayer exfoliation to obtain a uniform and stable graphene oxide slurry with a viscosity controlled at 300,000 mPa·s, good fluidity, and easy coating.

[0180] 3) Preparation of graphene oxide film

[0181] First, the graphene oxide slurry was degassed using a vacuum degassing system; then, it was transported to a comma coater through a pipeline and coated on a polypropylene substrate with a coating thickness of 5 mm, a speed of 5 m / min, a drying temperature of 100°C, and a drying time of 20 min; the dried graphene oxide film was peeled off from the polypropylene substrate and sliced ​​to obtain a 500 μm graphene oxide film.

[0182] 4) Carbonization and graphitization of graphene oxide films

[0183] First, under a nitrogen atmosphere, the oxidized ethylene film was sandwiched between two layers of graphite paper, placed in an oven, and heated to 600°C at a rate of 0.5°C / min and kept warm for 5 hours; then, under a nitrogen atmosphere, in a graphitization furnace, the temperature was raised to 3100°C at a rate of 30°C / min, kept warm for 0.5 hours, and naturally cooled to obtain an expanded graphene film.

[0184] 5) Graphene film calendering

[0185] Under vacuum conditions, the flat pressing process was used to maintain a pressure of 100 MPa for 60 minutes to compact the expanded graphene film and remove the gas generated between the graphene layers due to expansion, thus obtaining a flexible and highly thermally conductive graphene heat dissipation film with a Raman spectrum of ID / IG=0.02 and a density of 1.9 g / cm 3 , thickness is 500μm, and thermal conductivity is 1269W / (m·K).

[0186] Comparison and analysis of the petroleum-based graphene thermal conductive films prepared in Examples 1 to 10 and the graphene thermal conductive films prepared in Comparative Example 1 show that: in the products prepared in the embodiments of the present invention, the graphene is uniformly oxidized, the ratio of the amount of potassium permanganate used in the present invention to petroleum coke is 1-3, and the ratio of conventional graphite oxidation is 3-6, and the carbon content of the prepared graphite oxide is 60±5wt%. The amount of potassium permanganate oxidant used is significantly reduced, and the graphite oxide obtained by oxidation has a lower degree of oxidation, a low degree of oxidation and uniform oxidation, so the mass concentration of the oxidized petroleum coke slurry prepared in the present invention can reach 10%, and the concentration of the graphene oxide slurry prepared by conventional graphite oxide is only 5%. Various parameters of the embodiments of the present invention are better than those of the comparative examples, especially, the thickness of the graphene heat dissipation film prepared in Example 4 reaches 500μm, which is much higher than 23μm in Comparative Example 1. At the same time, the thermal conductivity of the graphene film obtained in Example 4 can reach 1712W / (m·K), which is also higher than 1600W / (m·K) in Comparative Example 1.

[0187] Comparison and analysis of the petroleum-based graphene thermal conductive films obtained in Examples 1 to 10 and the graphene thermal conductive films obtained in Comparative Example 2 show that: Comparative Example 2 uses natural graphite as raw material, and the natural graphite has fewer defects and larger size. The oxidation process proceeds from the edge to the middle, so it is difficult to oxidize uniformly, the boundary oxidation degree is high, and the middle oxidation degree is low; secondly, due to fewer defects, the size of the obtained single-layer graphene oxide is larger, so the viscosity of the obtained graphene oxide slurry is larger, it is difficult to evenly coat the film, and the uniformity of the obtained graphene oxide film is poor. Therefore, the thermal conductivity of the graphene film obtained in Comparative Example 2 is only 1267W / (m·K), which is much lower than 1712W / (m·K) of Example 4.

[0188] Comparison and analysis of the petroleum-based graphene thermal conductive films obtained in Examples 1 to 10 and the graphene thermal conductive films obtained in Comparative Example 3 show that: Comparative Example 3 uses artificial graphite as raw material, and artificial graphite has many defects and uneven size distribution, which makes it difficult to oxidize evenly, and graphite of different sizes has different oxidation degrees; secondly, the different oxidation degrees lead to poor uniformity of the oxidized graphene film, and the different reduction degrees during the carbonization-graphitization process lead to large differences in the expansion degree of different regions, making it difficult to obtain uniform graphene by calendering later. Therefore, the thermal conductivity of the graphene film obtained in Comparative Example 3 is only 985W / (m·K), which is much lower than 1712W / (m·K) of Example 4.

[0189] Comparison and analysis of the petroleum-based graphene thermal conductive films obtained in Examples 1 to 10 and the graphene thermal conductive films obtained in Comparative Example 4 show that: Comparative Example 4 uses expanded graphite as a raw material, and the expanded graphite has many defects and a large interlayer distance of the expanded graphite, which results in the rapid dispersion of the oxidant into the expanded graphite, a rapid oxidation degree, and further increase in defects; in the carbonization-graphitization process, it is difficult to effectively repair too many defects. Therefore, the thermal conductivity of the graphene film obtained in Comparative Example 4 is only 1269W / (m·K), which is much lower than 1712W / (m·K) of Example 4.

Claims

1. A method for preparing a graphene thermally conductive film, characterized in that: include: 1) petroleum coke powder is added to concentrated sulfuric acid and potassium permanganate to react to obtain oxidized petroleum coke; 2) dispersing the oxidized petroleum coke prepared in step 1) in deionized water and homogenizing it into a single-layer oxidized petroleum coke slurry.

2. The method according to claim 1, characterized in that Also includes: 3) Preparation of oxidized petroleum coke membrane Use a vacuum degassing system to degas the oxidized petroleum coke slurry, then apply the coating and dry it; An oxidized petroleum coke film is obtained.

3. The method according to claim 2, characterized in that Also includes: 4) Carbonization and graphitization of oxidized petroleum coke films Under nitrogen atmosphere, the oxidized petroleum coke film obtained in step 3) is sandwiched between two layers of graphite paper, baked at 600-1100° C. for carbonization, and graphitized at 2800-3100° C.

4. The method according to claim 3, characterized in that Also includes: 5) Graphene film calendering Under vacuum conditions, a flat pressing process is used to maintain a pressure of 100 MPa for 10 minutes to compact the expanded graphene film and remove the gas generated between the graphene layers due to expansion, thereby obtaining a flexible and highly thermally conductive graphene heat dissipation film.

5. The method of claim 1, wherein: The step 1) is to prepare oxidized petroleum coke by oxidizing petroleum coke through a modified Hummer process.

6. The method of claim 5, characterized in that: The modified Hummer process for oxidizing petroleum coke refers to: according to the mass ratio of concentrated sulfuric acid volume to petroleum coke of 10-60 ml / g, petroleum coke and concentrated sulfuric acid are mixed evenly, potassium permanganate is added under certain water bath temperature conditions, wherein the mass ratio of potassium permanganate to petroleum coke is 1-3, the temperature is raised to 20-100° C. and reacted for 0.2-6 hours, according to the mass ratio of distilled water volume to petroleum coke of 10-100 ml / g, distilled water is added, the reaction is carried out at 70-100° C. for 10-70 minutes, and then the oxidation reaction is terminated by dilution with distilled water, the volume ratio of distilled water added to the mass ratio of petroleum coke is 50-200 ml / g, and finally a certain amount of hydrogen peroxide is added to remove excess potassium permanganate, and the oxidized petroleum coke system is washed to a pH between 4 and 6.

7. The method of claim 1, wherein: The step 2) is as follows: dispersing the oxidized petroleum coke prepared in step 1) in deionized water to prepare an oxidized petroleum coke suspension with a mass concentration of 50 to 100 g / L, peeling the oxidized petroleum coke suspension with a high-pressure homogenizer, homogenizing at a pressure of 30 to 120 MPa to achieve single-layer peeling, and obtaining a uniform and stable oxidized petroleum coke slurry with a size of 0.1 to 0.9 μm, and controlling the slurry viscosity to be 50,000 to 350,000 mPa·S.

8. A method for preparing a graphene thermally conductive film according to any one of claims 1 to 7, characterized in that: Raman spectroscopy analysis of the graphene thermal conductive film I D / I G =0.01~0.03, density is 1.8~2.1g / cm 3 .

9. The graphene thermally conductive film according to claim 8, characterized in that: The Raman spectrum of the graphene thermal conductive film is ID / IG=0.01, and the density is 2.1 g / cm 3 .

10. An electronic product, characterized in that: The electronic product uses the petroleum-based graphene thermal conductive film described in any one of claims 8 or 9.

Citation Information

Patent Citations

  • Graphene thermal-conductive film / thermal-conductive silica gel film composite material with layered alternative structure and preparation method of composite material

    CN108819360A

  • Petroleum liquid product-based graphene quantum dot, and preparation method and application thereof

    CN108996492A

  • Method for preparing graphene heat-conducting film

    CN114774087A

  • Graphene heat conduction film applied to mobile phone and tablet personal computer

    CN210578669U

  • Graphene heat-conducting film structure applied to electronic product

    CN215321191U